1999
DOI: 10.1521/pedi.1999.13.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Facial Expression Recognition Ability Among Women with Borderline Personality Disorder: Implications for Emotion Regulation?

Abstract: This study examined recognition of facial expressions of emotion among women diagnosed with borderline personality disorder (BPD; n = 21), compared to a group of women with histories of childhood sexual abuse with no current or prior diagnosis of BPD (n = 21) and a group of women with no history of sexual abuse or BPD (n = 20). Facial recognition was assessed by a slide set developed by Ekman and Matsumoto (Japanese and Caucasian Facial Expressions of Emotion and Neutral Faces, 1992), expanded and improved fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
183
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(206 citation statements)
references
References 1 publication
19
183
1
3
Order By: Relevance
“…In a study in which the Ekman faces were used, Wagner and Linehan (1999) found that, compared with healthy control subjects, BPD patients were able to identify human facial expressions accurately in all cases except for neutral faces (the same stimuli that we have used), for which they tended to make errors and consigned negative emotions to those faces. In the present study, the most striking difference between the BPD and NC groups was the much greater incidence of BPD patients projecting negative attributes onto the Ekman faces.…”
Section: Discussionmentioning
confidence: 79%
“…In a study in which the Ekman faces were used, Wagner and Linehan (1999) found that, compared with healthy control subjects, BPD patients were able to identify human facial expressions accurately in all cases except for neutral faces (the same stimuli that we have used), for which they tended to make errors and consigned negative emotions to those faces. In the present study, the most striking difference between the BPD and NC groups was the much greater incidence of BPD patients projecting negative attributes onto the Ekman faces.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, Wagner and Linehan asked participants to verbally describe the emotional state of the presented person. Using this approach, they were able to show enhanced facial emotion recognition in the BPD group for fearful faces and a tendency in this group to over-report fear when presented with neutral facial expressions (Wagner & Linehan, 1999). This effect was interpreted as reflecting a negativity bias in the evaluation of ambiguous facial expressions in BPD.…”
Section: Facial Emotion Recognition In Bpdmentioning
confidence: 89%
“…Accordingly, BPD patients have been expected to show enhanced social sensitivity, which is reflected by increased vigilance for social cues, especially for cues that signal social rejection or threat (Wagner & Linehan, 1999). Thus, it has been assumed that BPD patients show enhanced sensitivity to facial emotional expressions, resulting in a lower detection threshold and increased accuracy in the detection of emotions.…”
Section: Facial Emotion Recognition In Bpdmentioning
confidence: 99%
“…Indeed, rather than reporting impaired emotion recognition associated with BPD, Wagner and Linehan (1999) found that women with BPD (all of whom had experienced child sexual abuse) were more accurate in their recognition of fear than both healthy female controls and women who had experienced childhood sexual abuse (but who did not have BPD). Women with BPD also showed a tendency to report Emotion Perception and Borderline PD 5 seeing fear in slides that did not contain fear, suggesting a bias toward fear recognition, even in the absence of fear cues.…”
Section: Introductionmentioning
confidence: 89%
“…Although some investigators report that people with BPD generally perform more poorly than controls on tests of emotion recognition (Bland et al, 2004;Unoka et al, 2011) in other studies no differences in ability to recognize emotions in static photographs of emotional faces have been found (Dyck et al, 2009;Minzenberg et al, 2006;Wagner and Linehan, 1999). Indeed, rather than reporting impaired emotion recognition associated with BPD, Wagner and Linehan (1999) found that women with BPD (all of whom had experienced child sexual abuse) were more accurate in their recognition of fear than both healthy female controls and women who had experienced childhood sexual abuse (but who did not have BPD).…”
Section: Introductionmentioning
confidence: 94%